Molecular genetic and morphological characteristics of Micractinium thermotolerans and M. inermum (Trebouxiophyceae, Chlorophyta) from pyroclastic deposits of the Kamchatka Peninsula (Russia) - R. Z. Sushchenko; V. Yu. Nikulin; V. B. Bagmet; A. Yu. Nikulin (Вавиловский журнал генетики и селекции, 2024)
During the study of algal diversity in pyroclastic deposits of the Kamchatka Peninsula, Chlorella-like green algae strains VCA-72 and VCA-93 were isolated from samples collected from along the Baydarnaya river bed on the Shiveluch volcano in 2018 and at the outlet of thermal vapors along the edge of the caldera on the southern slope of the Gorely volcano in 2020. Identification of the strains was carried out within the framework of an integrative approach using microscopic and molecular genetic methods, including preliminary taxon identification, obtaining nucleotide sequences of the small subunit and the internal transcribed spacer rRNA, reconstruction of phylogenetic trees and secondary structures of the ITS1 and ITS2 rRNA regions. On the phylogenetic tree, strain VCA-93 was clustered in the Micractinium thermotolerans species clade. No differences were found when comparing the helical domain models of ITS1 and ITS2 in M. thermotolerans. Strain VCA-72 occupied a basal position in the M. inermum clade. The secondary structure patterns of the helices of strain VCA-72 were generally similar to those of M. inermum, but intraspecific variability was noted, mainly due to substitutions in the apical and lateral loops. Five hCBC substitutions were found in the helical regions of the studied M. inermum strains, while no CBC substitutions were found. A detailed analysis of morphology and life cycle allowed us to identify the characteristics of the cells in aging cultures: their size was significantly higher than in vegetative ones and they were pear-shaped, oval, and ellipsoidal with a shallow, wide constriction in the center. In addition, cells with colorless lipid droplets were detected in aging cultures of both species. The ability to synthesize and accumulate lipids indicates the great potential of the strains for the production of biodiesel fuel. A review of the habitats of previous and new findings allowed us to note the ecological plasticity of the studied species. The results obtained complement the information on the biogeography of the species: this is the first record of M. inermum for the territory of Russia, and that of M. thermotolerans, for the Kamchatka Peninsula.